Total Synthesis and Biological Evaluation of Kakeromamide A and Its Analogues - Zhao, Meng; Xiao, Yi; Otsuka, Satoshi; Nakao, Yoichi; Guo, Yian; Ye, Tao (Frontiers in Chemistry, 2020)
Kakeromamide A (1), the first marine cyclopeptide inducing neural stem cells differentiation into astrocytes, was synthesized in 12 longest linear steps and 14% overall yield. Using this synthetic approach, four analogues of kakeromamide A were prepared and evaluated for neural differentiation- modulating activity.